PENEGAKAN HUKUM TERHADAP DELIK PENODAAN AGAMA - Saru Arifin (Program Studi Ilmu Agama Islam Program Magister, Universitas Islam Indonesia, 2008)
This research attempts to analyze the argumentations or factors which is used by government to any beliefer of religion conduct to be subjected as a breaker of criminal act related to religion, and what does it relation to a freedom of expressing a bilief as apart of human rights. This is a normatif-juridic research, and with the case and comparative approach. There are two data used in this research, both are primary and secondary data. The result of this research shows that parameters used by the government to criminalize any biliefer conduct is refer to the national act related to blasphemy, especially in the Article 156b KUHP. The three cases are studied in this research, Lia Eden, Yusman Roy and Ahmadiyah, profed broke of the religion bilief, both are blasphemy and Godslastering. This fact based on the evidences of their activities and also by expert opinion.